Food and intangible heritage, a flavourful relationship - United Nations Educational, Scientific; Cultural Organization; Lucia Iglesias Kuntz (The UNESCO Courier, 2025)
Some fifty traditional culinary practices are inscribed on UNESCO’s lists of intangible cultural heritage.